1984
DOI: 10.1080/0013191840360304
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Handwriting Performance

Abstract: The legibility components (letter formation, spacing, alignment and size) and speed of handwriting were assessed for 575 children in grades 3 to 7. Interrater reliabilities were high (·69 to ·97) and test-retest reliability over one week was lower for legibility (·44 to ·84) than for speed (·93). In general, reliabilities were higher for the older children. Correlations among legibility components ranged from ·46 to •76, though a principal factor analysis indicated that letter formation, spacing, alignment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
91
5
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 10 publications
(11 reference statements)
11
91
5
1
Order By: Relevance
“…All children attended grades 2 or 3, had a mean age of 8 years (range: 7-10 years), and had received an average of 19.2 months (SD = 7.2) of instruction and practice in writing. We opted for this age group because the literature on handwriting development suggests that by the time a child reaches the end of second grade, his or her handwriting has become more or less automatic, organized, and readily available [1,15,31]. Thus, a deficiency in these qualities at the age of our pupils is likely to be a sign of a (developmental) problem.…”
Section: Participants and Selection Proceduresmentioning
confidence: 99%
“…All children attended grades 2 or 3, had a mean age of 8 years (range: 7-10 years), and had received an average of 19.2 months (SD = 7.2) of instruction and practice in writing. We opted for this age group because the literature on handwriting development suggests that by the time a child reaches the end of second grade, his or her handwriting has become more or less automatic, organized, and readily available [1,15,31]. Thus, a deficiency in these qualities at the age of our pupils is likely to be a sign of a (developmental) problem.…”
Section: Participants and Selection Proceduresmentioning
confidence: 99%
“…Nevertheless, the research strongly suggests that boys are more likely to be identified as having a handwriting problem than girls (Hamstra-Bletz & Blote, 1993;Rubin & Henderson, 1982), and research in the 1980s and 1990s confirmed that girls are generally better handwriters than boys (Graham & Miller, 1980), both on measures of overall quality and of letter formation (Hamstra-Bletz & Blote, 1990;Ziviani & Elkins, 1984). Girls also tend to write faster than boys (Berninger & Fuller, 1992;Biemiller et al, 1993;Ziviani, 1984).…”
Section: Handwriting Problemsmentioning
confidence: 99%
“…Speed has always been used as a performance measure in relation to writing (Ayres, 1912;Burt, 1921;Freeman, 1959;Grof, 1961;Gross et al, 1996;Peverly, 2006). Legibility was not assessed, as there does not seem to be any consensus about its evaluation as researchers such as Ayres (1912), Alston and Taylor (1984), Burt (1921), Freeman (1959), Feldt (1962, Gipps (1984), Helwig et al (1976), Rarick and Harris (1963), Rubin and Henderson (1982), Ziviani (1982) and Ziviani and Elkins (1984) have all proposed different ways to evaluate legibility.…”
Section: Methodsmentioning
confidence: 99%